A review of percutaneous transhepatic biliary drainage at a tertiary referral centre. Issue 12 (December 2016) - Asadi, H.; Hollingsworth, R.; Pennycooke, K.; Thanaratnam, P.; Given, M.; Keeling, A.; Lee, M.
Abstract : Aim: To review percutaneous biliary drainage (PBD) procedures performed in Beaumont Hospital, Dublin, Ireland, over a 6-year period, to determine the 30-day morbidity and mortality. Materials and methods: A total of 119 patients undergoing 193 PBD procedures were identified over a 6 year period. Of the patients, 6.7% (eight patients) had stone disease, 63% (75 patients) had a malignancy, and the remainder were diagnosed with other conditions. Standard techniques of PBD and biliary stent insertion were applied, with 73 patients (61%) having same-day procedures and all undergoing gelfoam embolisation of percutaneous tracts. All patients received intravenous prophylactic antibiotics and intravenous hydration prior to PBD. Results: The technical success rate was 97%, with a mean drop of 105 mmol/l between pre- and post-procedure bilirubin. Thirty-day mortality was 10.9% (13 deaths), with major and minor morbidities of 5% (six patients) and 7.6% (nine patients), respectively. Major complications included sepsis in two patients, major haemorrhage in two patients, and renal failure in two patients. Minor complications included infection in seven patients, bile leak causing self-limiting pain in one patient, and minor haemorrhage in one patient. Conclusion: The study confirms that PBD and stent insertion is a safe and effective technique in Beaumont Hospital, associated with an overall acceptable morbidity and mortality comparable with other studies. Highlights: Our study demonstrated significantly lower morbidity and mortality compared with BSIR audit. However major complications associated with mortality were more or less the same. This is likely related to the strict pre- & post-procedural optimisation. Our protocol is based on quality improvement guidelines from CIRSE. Implementation of CIRSE practice guidelines decreases PTBD morbidity and mortality.